A highly hydrated α‐cyclodextrin/1‐undecanol inclusion complex: crystal structure and hydrogen‐bond network from high‐resolution neutron diffraction at 20 K. (26th February 2013) - Gallois‐Montbrun, Delphine; Le Bas, Geneviève; Mason, Sax A.; Prangé, Thierry; Lesieur, Sylviane
<x xml:space="preserve">Abstract</x> The monoclinic C2 crystal structure of an α‐cyclodextrin/1‐undecanol host–guest inclusion complex was solved using single‐crystal neutron diffraction. Large high‐quality crystals were specially produced by optimizing temperature‐controlled growth conditions. The hydrate crystallizes in a channel‐type structure formed by head‐to‐head dimer units of α‐cyclodextrin molecules stacked like coins in a roll. The alkyl chain of the guest lipid is entirely embedded inside the tubular cavity delimited by the α‐cyclodextrin dimer and adopts an all‐trans planar zigzag conformation, while the alcohol polar head group is outside close to the α‐cyclodextrin primary hydroxyl groups. The cyclodextrin dimer forms columns, which adopt a quasi‐square arrangement much less compact than the quasi‐hexagonal close packing already observed in the less hydrated α‐cyclodextrin channel‐type structures usually found with similar linear guests. The lack of compactness of this crystal form is related to the high number of interstitial water molecules. The replacement of 1‐undecanol by 1‐decanol does not modify the overall crystal structure of the hydrate as shown by additional X‐ray diffraction investigations comparing the two host–guest assemblies. This is the first study that analyses the entire hydrogen‐bonding network involved in the formation of a cyclodextrin dimer surrounded by its shell of water molecules.